Two new species of the genus Ologamasus (Ologamasidae) from apple orchards in southern Brazil - Bizarro, Gabriel Lima; Rode, Priscila De Andrade; Schussler, Matheus; Costa, Tairis Da-; Ferla, Noeli Juarez (Zootaxa, 2023)
This paper describes two new species of the genus Ologamasus (Acari: Ologamasidae), namely Ologamasus margaridae n. sp. and Ologamasus tuberculatus n. sp., based on females, males and nymphal stages collected in apple orchards (Malus domestica Borkh.) in southern Brazil. Ologamasus tuberculatus has a distinctive pair of large pores inserted on protuberances on the dorsal shield.